Uso de silício e leveduras no manejo de Cercospora beticola Sacc. em beterraba açucareira e suas implicações bioquímicas e produtivas - Silva, Rayssa Helana da (2021)
Sugar beet productivity is reduced by the attack of Cercorpora beticola Sacc. however, the resistance acquired by the pathogen to fungicides, added to the need to reduce the environmental impact, require the use of alternative methods capable of increasing plant resistance to diseases. Therefore, this work aimed to control C. beticola with the aid of yeasts and calcium silicate, as well as to evaluate the biochemical and productive mechanisms triggered by the treatments. Thus, for field evaluations, a randomized block experimental design (DBC) was used in a 3 x 2 factorial scheme with five replications, with the treatments: Cryptococcus laurentii, Pichia pini and control, tested in the presence and absence of calcium silicate. Fresh and dry root mass, yield, sugar content determination and disease severity were evaluated. In a growth chamber, a design in DBC was used, with 4 treatments (C. laurentii, P. pini, silicon and control) and 6 replications, where the determination of total phenols, lignin, peroxidase activities, polyphenoloxidase and phenylalanine ammonia- lyase was carried out. There was no significant difference between treatments and there was no interaction between treatments and conditions in the field experiment, as well as no significance between treatments in the growth chamber experiment. Therefore, treatment with yeast and silicon did not promote gains in root or sugar yield, did not reduce disease severity and did not promote changes in the studied enzymes. There was a significant difference between the times used for protein, peroxidase, polyphenoloxidase and phenylalanine ammonia-lyase. Therefore, new tests with different doses of silicon and a greater number of yeast applications are necessary to observe the effectiveness of the treatment with silicon and yeast for sugar beet production and for disease control.